Physical variables - lake temperature profile from Tarfalasjön, temperature profiler, 2016-09-17–2019-09-05 - Tarfala Research Station (Stockholm University, 2020)
High frequency temperature profiles are measured in lakes of SITES Water to be able to determine the thermal structure.
Kirchner, N., Kuttenkeuler, J., Rosqvist, G., Hancke, M., Granebeck, A., Weckström, J., Weckström, K., Schenk, F., Korhola, A., Eriksson, P., 2020. Water temperatures from the arctic-alpine Lake Tarfala, Northern Sweden, 2016⁠ – ⁠2019. https://doi.org/10.17043/KIRCHNER-2020
Keywords: Tarfala Research Station; Lake; Time instant; Time instant; Water temperature; Water temperature; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap